Determination of Blood Lead Levels in Drivers at Marunda Terminal, North Jakarta, Using ICP-MS - Utama, Aditiya Tri; Sari, Elfira Maya; Amelia, Ria (Pustaka Media Publishing, 2025)
One of the elements that has the biggest impact of air pollution is lead. Lead can be contaminated through the air, one of which is produced by burning vehicles and releasing lead oxide in the form of dust or particles that can be inhaled into the human respiratory tract. The duration of lead exposure affects air pollution which can harm human health. The aim of this research was to determine blood lead levels in truck drivers in a section of Marunda terminal North Jakarta using the ICP-MS method. ICP-MS has multi-element analysis capabilities and high sensitivity compared to other techniques. This type of research is quantitative descriptive with a cross-sectional research design and data collection using purposive sampling, data collection was carried out in June 2023. Lead examination was carried out at the DKI Jakarta Regional Health Laboratory. The type of specimen used is human blood. Blood samples were collected using an EDTA tube and then measured using an ICP-MS device. The results showed that 17 respondents had lead levels < 2.28 µg/L. Blood lead levels in truck drivers in a section of Marunda terminal North Jakarta were not detected. This shows that there is no lead content in the blood.